Analisis penggunaan video pembelajaran dari youtube "Mandarin Corner" sebagai media belajar bagi pemula Bahasa Mandarin - Budiono, Tasya Negara Hapsari; Purnamasari, Bujur Ita (Fakultas Sastra Universitas Negeri Malang, 2022)
Language plays a role as a means of human communication in one country or even in various countries. In this regard, Mandarin was chosen as the second most widely spoken foreign language in the world after English. Therefore, many people want to learn Mandarin so that they can communicate more broadly. Beginners who decide to learn Mandarin should be supported by interactive and easy-to-understand learning media. This media for learning Chinese for beginners is the author's main focus, which is later expected to be able to support the academic achievements of Chinese language enthusiasts. The research method used is descriptive qualitative analysis. The research results obtained are the use of learning media through videos on Youtube is very helpful for beginners to learn Mandarin well, and this research chose the "Mandarin Corner" channel as the focus because it is very practical, easier to understand, and lots of basic materials are also available.